ARTICULAR CARTILAGE THICKNESS OF THE PEDIATRIC KNEE: IMPLICATIONS FOR CARTILAGE IMPLANTATIONS. Issue 3 (31st March 2019) - Rustad, Audrey; Anchustegui, Nicolas G.; Troyer, Stockton; Shea, Cooper; Dingel, Aleksei; Shea, Kevin
Background: While access to pediatric tissue for cartilage conditions is limited, recent research on the use of pediatric cartilage tissue for implantation has shown promising results. These pediatric grafts may include bulk osteochondral allografts, morselized cartilage, or cellular manipulation products. The purpose of this study was to evaluate the parameters of cartilage thickness in different regions of the pediatric knee from a larger pediatric knee specimen research database. Methods: CT Scans of 12 skeletally immature knees ranging from ages 7 to 11 were evaluated. Cartilage thickness measurements were taking in the following regions: 1. Femoral Condyles - Cahill Zones 1, 2, 4, and 5 (Fig. 1) on coronal plane CT images, the region of greatest cartilage thickness on medial and lateral femoral condyles using coronal plane CT images, and Cahill Zones A, B, and C on sagittal plane CT images (Fig. 2). 2. Tibial Plateau – the region of greatest cartilage thickness identified on the medial and lateral sides of the tibial plateau using coronal plane CT images (Fig. 1). 3. Patella – the region of greatest cartilage thickness identified on axial and sagittal CT images (Fig. 3 and 4). Results: The cartilage on the medial femoral condyle had an average thickness of 4.86 mm ± 0.61 mm at its thickest point and the cartilage on lateral femoral condyle had an average thickness of 3.71 mm ± 0.52 mm at its thickest point. The cartilage on the medial tibial plateau had an average thickness of 2.80 mm ± 0.26 mm at its thickest point and the cartilage on the lateral tibial plateau had an average thickness of 3.29 mm ± 0.45 mm at its thickets point. The cartilage on the midpoints of Cahill zones 1, 2, 3, and 4 had an average thickness of 2.93 mm ± 0.62 mm, 3.42 mm ± 0.66 mm, 2.81 mm ± 0.46 mm, and 3.30 mm ± 0.73 mm respectively. The cartilage on the midpoints of Cahill zones A, B, and C had an average thickness of 3.81 mm ± 0.68 mm, 4.40 mm ± 0.49 mm, and 3.82 mm ± 0.68 mm respectively. The cartilage at its thickest point on the patella had an average thickness of 4.53 mm ± 0.38 mm from an axial view and 4.40 mm ± 0.49 mm from a sagittal view (Fig. 5 and 6). Conclusion: Pediatric knees demonstrate relatively thick cartilage regions in multiple zone of the knee, compared with adult specimens. Increasing access to and use of this tissue for cartilage grafts, non-manipulated tissue, and manipulated tissue offer significant opportunity to address cartilage loss. Osteochondral allograft procedures may benefit from access to such tissue, with relatively high volume and thickness of normal articular cartilage. Figure 1. Method for measuring Cahill Midpoints 1, 2, 4, 5, MFC, LFC, MTP, and LTP Five anatomic regions (Cahill Zones 1, 2, 3, 4, and 5, with Zone 1 being the most medial) were created by bisecting the condyles and identifying the ends of the intercondylar notch. The width of the articular cartilage was then measured using the midpoints of Cahill Zones 1, 2, 4, and 5. The greatest cartilage thickness for the medial femoral condyle (MFC), lateral femoral condyle (LFC), medial tibial plateau (MTP), and lateral tibial plateau (LTP) were also measured. Figure 2. Method For Measuring Cahill Zones A, B, C A line from the metaphysis to the epiphysis divides zones B and C. Another line from the physis to the anterior portion of the physis divides zones A and B. The cartilage width at the midpoint of each of these zones was then measured. Figure 3. Measuring the greatest cartilage thickness on the patella (axial view). Figure 4. Measuring the greatest cartilage thickness on the patella (sagittal view). Figure 5. Average cartilage thickness for patella and femoral condyles Figure 6. Average cartilage thickness for tibial plateau